Initial studies on the cytotoxicity of ceramics prepared from dry discharge incinerator bottom ash dust. Issue 15 (15th November 2016) - Bourtsalas, A. (Thanos); Detsch, Rainer; Boccaccini, Aldo R.; Cheeseman, Christopher
Abstract: The dust generated from a dry discharge ash handling system at a waste to energy (WtE) facility has been processed and sintered to produce ceramic samples. Preliminary cell culture studies have been completed to assess the potential cytotoxicity of the IBA ceramics prepared from dry discharge dust. The tests have used mouse embryonic fibroblast (MEF) cells. Results indicate inhibition of cell adhesion by the IBA ceramic surface. However the samples were covered by cells and these expressed similar behaviour in the context of morphology and vitality to control cells on glass samples. The work demonstrates that fine IBA dust from dry discharge systems can be formed into ceramics and that biocompatibility testing has an important role in defining potential suitability for use of these types of waste-derived ceramics.